Beneficial Effects of Echinacoside on Diabetic Cardiomyopathy in Diabetic Db/Db Mice - Zhang X; Hao Y (Dove Medical Press, 2020)
Xiang Zhang, Yarong Hao Department of Geriatrics, Renmin Hospital of Wuhan University, Hubei, People’s Republic of ChinaCorrespondence: Yarong HaoDepartment of Geriatrics, Renmin Hospital of Wuhan University, 99 Zhang Zhidong Road, Wuchang District, Wuhan, Hubei Province, People’s Republic of ChinaTel +86 18827688568Email 984022801@qq.comPurpose: In this study, we investigated the protective effects and mechanism of action of echinacoside (ECH) from cistanche tubulosa extract in cardiomyocytes of db/db diabetic mice.Methods: Twenty healthy male db/db mice aged 8 weeks were randomly divided into db/db+ECH (n=10, ECH, 300 mg/(kg/d)), db/db (n=10, saline), and db/m control groups (n=9). Mice were monitored weekly for diet and activity. Mice were injected with 2% of pentobarbital sodium in week 10 and executed. Weight and free blood glucose (FBG) were measured weekly. Echocardiographs were used to detect cardiac function. HE staining, Sudan II staining, Masson’s trichrome staining and Tunel assays were used to evaluate myocardial tissue pathological changes, collagen fiber deposition, lipid accumulation and apoptosis rates in cardiomyocytes, respectively. Western blot and RT-PCR analysis were used to detect the expression of components of the PPAR-α/M-CPT-1 and p53/p38MAPK signaling axis.Results: Compared to db/db mice, ECH groups showed lower blood glucose and lipid levels. Deterioration in cardiac function was also delayed following ECH treatment. Histopathological analysis showed that ECH significantly improved myocardial tissue in db/db mice, including reduced intercellular spaces, regular arrangements, improved extracellular matrix deposition, and reduced lipid accumulation. ECH also significantly reduced oxidative stress levels in myocardial tissue in db/db mice. Moreover, ECH inhibited PPAR-α/M-CPT-1 signaling, downregulated CD36, and upregulated glucose transporter type 4 (GLUT-4) expression in db/db mouse models of DCM. ECH also inhibited p53/p38MAPK signaling, downregulated caspase-3 and caspase-8, and upregulated Bcl-2/Bax in db/db mouse models of DCM.Conclusion: ECH displays protective effects in DCM, including the inhibition of cardiac apoptosis and oxidative stress, and improved lipid metabolism in cardiomyocytes. ECH also inhibits cardiac apoptosis through its regulation of p53/p38MAPK signaling, and prevents lipid accumulation through suppression of the PPAR-α/M-CPT-1 signaling axis.Keywords: diabetic cardiomyopathy, echinacoside, lipid metabolism disorders, PPAR-α, p53/p38MAPK signaling